2017
DOI: 10.1002/job.2241
|View full text |Cite
|
Sign up to set email alerts
|

Perceived mastery climate, felt trust, and knowledge sharing

Abstract: Interpersonal trust is associated with a range of adaptive outcomes, including knowledge sharing.However, to date, our knowledge of antecedents and consequences of employees feeling trusted by supervisors in organizations remains limited. On the basis of a multisource, multiwave field study among 956 employees from 5 Norwegian organizations, we examined the predictive roles of perceived mastery climate and employee felt trust for employees' knowledge sharing. Drawing on the achievement goal theory, we develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 128 publications
(261 reference statements)
5
98
2
Order By: Relevance
“…In a review, Wang and Noe [32] concluded that trust is an antecedent of knowledge sharing that needs further research attention. This study re-validates previous literature that found a positive significant relationship role of trust in influencing knowledge sharing [49,50] in an emerging economy (i.e., Kenya). The results are significant as it shows that even in a culture where management does not make knowledge management processes a priority [23,24], the link between trust and knowledge sharing still holds.…”
Section: Theoretical Contributionssupporting
confidence: 89%
See 2 more Smart Citations
“…In a review, Wang and Noe [32] concluded that trust is an antecedent of knowledge sharing that needs further research attention. This study re-validates previous literature that found a positive significant relationship role of trust in influencing knowledge sharing [49,50] in an emerging economy (i.e., Kenya). The results are significant as it shows that even in a culture where management does not make knowledge management processes a priority [23,24], the link between trust and knowledge sharing still holds.…”
Section: Theoretical Contributionssupporting
confidence: 89%
“…That is, individuals are more likely to recognize the value and apply the new knowledge when the giver is someone they trust [48]. Following extant literature that support this rationale [49,50], the following hypothesis was developed.…”
Section: Coworker Trust and Knowledge Sharingmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars suggest that the perception of a mastery climate may encourage the intentions and intrinsic motivation of individuals to perform actively at the workplace (Sproule, John Wang, Morgan, McNeill, & McMorris, 2007). Nerstad et al (2018) concluded that PMMC creates more trust among employees and between supervisors and employees at individual and team levels. In addition, PMMC fosters knowledge sharing behavior among workers and supervisors (Nerstad et al, 2018).…”
Section: Moderating Role Of Pmmcmentioning
confidence: 99%
“…The emphasis is on comparing employees’ present level of performance with their prior achievements. Research has shown that a mastery climate typically produces several adaptive consequences, such as higher performance, work engagement, mastery orientation, creativity, intrinsic motivation, and knowledge sharing (Buch, Nerstad & Säfenbom, ; Černe, Nerstad, Dysvik & Škerlavaj, ; Harwood, Keegan, Smith & Raine, ; Nerstad et al ., ; Nerstad, Searle, Černe, Dysvik, Škerlavaj & Scherer, ). For example, Nerstad et al .…”
Section: Theory and Hypothesesmentioning
confidence: 99%